2020
DOI: 10.3389/fpsyg.2020.01349
|View full text |Cite
|
Sign up to set email alerts
|

Line-Up Image Position in Simultaneous and Sequential Line-Ups: The Effects of Age and Viewing Distance on Selection Patterns

Abstract: It is known that children and older adults produce more false alarms in target absent line-ups and that weaker facial encoding increases choosing bias. However, there has been no investigation of how age or facial encoding strength impacts line-up position selections in either sequential or simultaneous line-ups. In the present study, we presented participants with four live targets (one by one) while manipulating sequential and simultaneous line-ups between participants and target present and target absent li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The analysis showed that target voices in earlier positions resulted in accuracy rates that were almost double the accuracy for later positions. This indicates that serial voice parades suffer from the same “unwanted position effects” found in sequential eyewitness lineups (Meisters et al, 2018; Nyman et al, 2020). One explanation for this is that more auditory attentional resources are available in the beginning of a voice parade compared with voices later in the parade.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The analysis showed that target voices in earlier positions resulted in accuracy rates that were almost double the accuracy for later positions. This indicates that serial voice parades suffer from the same “unwanted position effects” found in sequential eyewitness lineups (Meisters et al, 2018; Nyman et al, 2020). One explanation for this is that more auditory attentional resources are available in the beginning of a voice parade compared with voices later in the parade.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, we found strong evidence that “unwanted position effects” were present in both experiments indicating that listeners in both the nine- and six-voice parades were substantially more likely to identify the target correctly when it appeared in an early position compared with a late position. While position effects have not been studied previously in voice identification research, there is some evidence that listeners are more likely to pick early faces in sequential eyewitness lineups (e.g., Nyman et al, 2020). We discuss the potential implications of these findings below.…”
Section: Methodsmentioning
confidence: 99%